2018
DOI: 10.4103/2347-5625.217443
|View full text |Cite
|
Sign up to set email alerts
|

Palliative chemotherapy: The perspectives and experiences of south african nurses

Abstract: Objective:The objective of this study was to describe the perspectives and experiences of South African nurses caring for patients receiving palliative chemotherapy.Methods:A qualitative descriptive design was used and purposive sampling allowed us to select 11 nurses practising in a private ambulatory cancer care center in Port Elizabeth. In-depth interviews, guided by three broad themes were conducted and analyzed using qualitative content analyses. Data saturation determined the sample size.Results:Two them… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
(25 reference statements)
0
4
0
1
Order By: Relevance
“…However, an alternative perspective on hope was also noted, emphasizing that some patients cling to hope because it is what makes life meaningful for them, and they may resist redirecting their hope towards more realistic goals [ 23 ]. Additionally, the study revealed that patients didn’t always make the decision to undergo palliative chemotherapy entirely on their own; some felt pressure from their families [ 8 ]. The role of others in patients’ palliative chemotherapy decisions varied, with different studies showing different patterns of decision-making, either involving doctors, patients themselves, or family influence [ 24 , 25 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, an alternative perspective on hope was also noted, emphasizing that some patients cling to hope because it is what makes life meaningful for them, and they may resist redirecting their hope towards more realistic goals [ 23 ]. Additionally, the study revealed that patients didn’t always make the decision to undergo palliative chemotherapy entirely on their own; some felt pressure from their families [ 8 ]. The role of others in patients’ palliative chemotherapy decisions varied, with different studies showing different patterns of decision-making, either involving doctors, patients themselves, or family influence [ 24 , 25 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the study revealed that patients didn’t always make the decision to undergo palliative chemotherapy entirely on their own; some felt pressure from their families [ 8 ]. The role of others in patients’ palliative chemotherapy decisions varied, with different studies showing different patterns of decision-making, either involving doctors, patients themselves, or family influence [ 24 , 25 , 8 ]. Some patients may not be entirely transparent about their well-being due to concerns that their treatment might be stopped.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Como em toda equipe de saúde, o papel do enfermeiro é primordial e indispensável na assistência ao paciente oncológico, proporcionando melhor conforto aos pacientes e familiares, na fase final de vida (Matzo, 2016;Souza, 2011). O enfermeiro é o profissional que se encontra a maior parte do tempo ao lado do paciente durante todo o seu tratamento (Maree & Potgieter, 2018). Enquanto houver vida, existe o cuidado de enfermagem, mesmo para uma doença incurável (Matzo, 2016).…”
Section: Competências E Cuidados De Enfermagem Na Quimioterapia Paliaunclassified
“…Purposive sampling refers to the procedure wherein the researcher employs their own discretion to select participants who possess unique and specialised information regarding the topic that is under research (Rahi, 2017). Maree and Potgieter (2018) and Korstjens and Moser (2018) state that sampling is the process of choosing or looking for circumstances, environments, and/or participants who provide rich data on the phenomenon of interest. Since a qualitative case study focuses on a limited number of varied groups, the sample size is often modest (Windsong, 2018).…”
Section: Samplingmentioning
confidence: 99%